Penanaman Nilai-Nilai Keagamaan Melalui Ekstrakurikuler Seni Hadroh di Madrasah Diniyah Miftahul ‘Ulum Kesugihan, Pulung, Ponorogo - Muhammad Nurdi; Diyan Putri Ayu (Institut Agama Islam Sunan Giri Ponorogo, 2025)
In Hadroh art, there are so many values that are connected with education aspects like divinity (tauhid), worship, and characteristic. At Madrasah Diniyah Miftahul ‘Ulum Kesugihan Pulung, Hadroh extracuricullar is one of the subject that becomes one of vessel in Madrasah’s way to plant characterisctic values to students. According to the background above that problem’s formulation in this research is (1) how the Hadroh’s extracuricurral activity process in Madrasah Diniyah Miftahul ‘Ulum Kesugihan Pulung, (2) any characteristic values that could be formed through Hadroh extracuricullar activity. This is a qualitative research, kind of field research that takes the place in Madrasah Diniyah Miftahul ‘Ulum Kesugihan Pulung. Data accumulation metode that was used are observation, interview, and documentation. In carrying out this community service using the Assest Based Community Development (ABCD) method with 5 (five) stages of activity namely discovery, dream, design, define, and destiny. This research’s result indicates that Hadroh extraculicullar in Madrasah Diniyah Miftahul ‘Ulum Kesugihan Pulung which is followed by 12 male students III, IV, V and VI where the event’s sequences in every practice are opening, vocal material giving and tabuhan, sholawat reading (song making), and closing. Characteristic values that improved in Hadroh extracullicular are religious, dicipline, hard work, independence, curiosity, patriotism (nationalism), recognize excellence, and responsibility.